2018
DOI: 10.1111/jzs.12239
|View full text |Cite
|
Sign up to set email alerts
|

Geographic patterns of postzygotic isolation between two closely related widespread dung fly species (Sepsis cynipseaandSepsis neocynipsea; Diptera: Sepsidae)

Abstract: Identifying the contribution of pre‐ and postzygotic barriers to gene flow is a key goal of speciation research. The widespread dung fly species Sepsis cynipsea and Sepsis neocynipsea offer great potential for studying the speciation process over a range of opportunities for gene exchange within and across sister species (cross‐continental allopatry, continental parapatry and sympatry). We examined the role of postcopulatory isolating barriers by comparing female fecundity and egg‐to‐adult viability of F1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 67 publications
(119 reference statements)
1
26
0
Order By: Relevance
“…Most crucially, however, our study does not support the often-raised prediction that sexually selected traits (here the male foreleg) evolve faster than naturally selected traits (here the wing; Arnqvist, 1998;Arnqvist & Rowe, 2005). Given that all investigated European S. neocynipsea populations are sympatric with S. cynipsea, we additionally detected slightly stronger fore femur differentiation in sympatry versus cross-continental allopatry (presumably due to character displacement: Giesen et al, 2017;Giesen et al, 2019). Whether sexual selection acts not only on the male forelegs but perhaps also the male wings remains to be directly assessed.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Most crucially, however, our study does not support the often-raised prediction that sexually selected traits (here the male foreleg) evolve faster than naturally selected traits (here the wing; Arnqvist, 1998;Arnqvist & Rowe, 2005). Given that all investigated European S. neocynipsea populations are sympatric with S. cynipsea, we additionally detected slightly stronger fore femur differentiation in sympatry versus cross-continental allopatry (presumably due to character displacement: Giesen et al, 2017;Giesen et al, 2019). Whether sexual selection acts not only on the male forelegs but perhaps also the male wings remains to be directly assessed.…”
Section: Discussionmentioning
confidence: 80%
“…Sexual selection is considered an important evolutionary force that may not only lead to rapid trait diversification, but also promotes population differentiation and speciation (Arnqvist & Rowe, ; Hosken & Stockley, ). Our quantitative genetic breeding design uncovered significant differentiation in fore femur shape among the two closely related sister species, as well as between the continental populations of S. neocynipsea , which are likely undergoing incipient speciation in allopatry (Giesen et al, , ). However, the differentiation of femur morphology was of similar magnitude as that of wing vein positioning, which refutes our original prediction that male ornaments evolve at a higher rate than wings.…”
Section: Discussionmentioning
confidence: 96%
“…Rohner et al 2015, Rohner 2015, Rohner and Bächli 2016. These two species hybridize readily in the laboratory, though hybridization is apparently prevented in nature by behavioural incompatibility (Giesen et al 2017(Giesen et al , 2018. Rohner et al (2015) demonstrated greater sepsid species richness at higher altitudes in the Swiss Alps.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that S. cynipsea and S. neocynipsea produce fertile hybrid offspring under laboratory conditions despite strong pre-and postmating isolating barriers. These barriers are mediated by assortative mating behaviors that are partly reinforced in areas where the two species occur in sympatry (Giesen et al, 2017(Giesen et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, less gene flow in sympatry than in allopatry would indicate selection against gene flow and thus suggest reinforcement of reproductive barriers at sites of co-occurrence (Butlin, 1995;Noor, 1999;Coyne & Orr, 2004;e.g. Kulathinal & Singh, 2000;Massie & Makow, 2005;Giesen et al 2017Giesen et al , 2019.…”
Section: Introductionmentioning
confidence: 99%